LITERATURE REVIEW : DETEKSI BOLA DENGAN METODE YOLO PADA SEPAK BOLA - Rivan Saghita Pratama; Indra Ramadhan; Niko Bagaskara; Vedo Septiano H (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores object recognition in soccer-playing robots using omnidirectional visual sensors and real-time YOLO detection. A systematic literature review of 52 articles (2020–2025) analyzes YOLO's development in robotic soccer. Findings show that robots can detect multiple objects like balls and goals in real-time with high accuracy. Factors such as lighting, object distance, and background complexity affect detection performance. The use of 360-degree cameras enhances the robots' ability to identify objects from all directions, improving their navigation and strategy during matches.